Synthesis and characterization of a novel peptide-grafted Cs and evaluation of its nanoparticles for the oral delivery of insulin, in vitro, and in vivo study - Barbari GR (Dove Medical Press, 2018)
Ghullam Reza Barbari,1 Farid Dorkoosh,1 Mohsen Amini,2 Nika Bahari Javan,1 Mohammad Sharifzadeh,3 Fateme Atyabi,1 Saeed Balalaie,4 Niyousha Rafiee Tehrani,5 Morteza Rafiee Tehrani1 1Department of Pharmaceutics, School of Pharmacy, Tehran University of Medical Sciences, Tehran, Iran; 2Department of Medicinal Chemistry, School of Pharmacy, Tehran University of Medical Sciences, Tehran, Iran; 3Department of Pharmacology, School of Pharmacy, Tehran University of Medical Sciences, Tehran, Iran; 4Department of Chemistry, Khajeh Nasir Toosi University, Tehran, Iran; 5School of Medicine, Tehran University of Medical Sciences, Tehran, Iran Background: Despite years of experience and rigorous research, injectable insulin is the sole trusted treatment method to control the blood glucose level in diabetes type 1 patients, but injection of insulin is painful and poses a lot of stress to the patients, especially children, therefore, development of a non-injectable formulation of insulin is a major breakthrough in the history of medicine and pharmaceutical sciences. Methods: In this study, a novel peptide grafted derivative of chitosan (CPP-g- chitosan) is synthesized and its potential for oral delivery of proteins and peptides is evaluated. Drug-loaded nanoparticles were developed from this derivative using ionic gelation method with application of sodium tripolyphosphate (TPP) as a cross-linking agent. Human insulin was used as the model protein drug and release kinetic was studied at gastrointestinal pH. Finally the developed nanoparticles were filled into very tiny enteric protective capsules and its effects on blood glucose level are evaluated in laboratory animals. Results: Presence of the positively charged cell-penetrating peptide moiety in the structure of chitosan polymer had slight inhibitory effects on the release of insulin from the nanoparticles in simulated gastric fluid (pH 1.2) comparing to native chitosan. The nanoparticles were positively charged in gastrointestinal pH with size ranging from 180 nm to 326 nm. The polypeptide grafted to chitosan is a novel analog of Penetratin, presenting both the hydrophilic and hydrophobic characteristics altering the release behavior of the nanoparticles and significantly increase the absorption of insulin into the rat epithelium comparing to nanoparticles from simple chitosan. In-vivo results in diabetic rat proved that this nanoparticulate system can significantly lower the blood glucose levels in diabetic rats and remain effective for a duration of 9–11 hours. Conclusion: The results indicate that nanoparticles developed from this new peptide conjugated derivative of chitosan are very promising for oral delivery of proteins and peptides. Keywords: peptide grafted, oral delivery, cell-penetrating peptide, penetratin